Proposal of a functional prognostic scale in mexican patients with Guillain-Barré syndrome - Edwin S. Vargas-Cañas; Juan C. López-Hernández; Sandra Badial-Ochoa; Javier Galnares-Olalde; Victoria Martínez-Angeles; Elliot Hernández-Angelino; David Domínguez-Romero; Raúl Medina-Rioja (Revista de Investigación Clínica, 2024)
Background: There is currently no prognostic scale for patients with Guillain-Barré syndrome (GBS) in the Mexican population. Objective: The objective of the study was to examine the factors associated with functional prognosis by proposing short-term and long-term prognostic scales. Methods: Prospective cohort of patients with GBS at an academic medical center, with neuroconduction study and 6-month follow-up. Through logistic regression, we evaluated clinical and paraclinical variables,\\r\\nand the results are expressed as odds ratios 95% confidence intervals [CIs]). We used a scale to predict poor functional prognosis. The performance of the scale was assessed using the area under the curve (AUC). Results: A total of 259 patients (age 46.1 +- 16.1 years) were included in the study; 38.6% had a history of diarrhea, and 42.8% had an axonal variant. The rates of poor functional prognosis were 36.6% and 22.7% at 3 and 6 months of follow-up, respectively. The following variables were included in the univariate logistic regression: age >- 70 years, history of diarrhea, axonal variant, and Medical Research Council score. We performed a prognostic scale (0-9 points), with AUC of 0.81 (95% CI: 0.75-0.86) at 3 months, and 0.82 (95% CI: 0.76-0.87) at 6 months, which was higher than the modified Erasmus Guillain-Barré Outcome Score scale at admission (AUC: 0.75. 95% CI: 0.69-0.81 and AUC: 0.78. 95% CI: 0.72-0.83). Conclusion: The proposed prognostic scale performs well in discerning poor functional prognosis in short- and long-term frames among Mexican patients.